Cochrane Database of Systematic Reviews 2003
DOI: 10.1002/14651858.cd003973
|View full text |Cite|
|
Sign up to set email alerts
|

Human menopausal gonadotropin versus recombinant follicle stimulation hormone for ovarian stimulation in assisted reproductive cycles

Abstract: For all three GnRHa protocols analysed there is insufficient evidence of a difference between hMG and rFSH on ongoing pregnancy or live birth. More large randomised trials are needed to estimate the difference between hMG and rFSH more precisely. Such trials should preferably (1) use a consistent long GnRHa protocol and (2) use a fixed dose of gonadotrophin such to prevent potentially subjective decisions of the clinician in dosing and (3) take live birth as primary endpoint. At this moment in time however, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…From 30 publications comparing r-hFSH versus hMG in ART, seven were meta-analyses/reviews (Al-Inany [2003, 2005, 2008, 2009], Westergaard, Coomarasamy, Afnan), four were excluded as duplicate publications (Plateau [2004, 2008], Smitz, Ziebe) and three studies were excluded because of insufficient details (Elwin [unpublished data], Loutradis, Strowitski) [1,2,13,18,23,26,30-32,42-45]. The 16 remaining studies which were truly or quasi-randomized met the inclusion criteria and were found to be of acceptable internal validity [5,14-17,19-22,24,25,27-29,46,47].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…From 30 publications comparing r-hFSH versus hMG in ART, seven were meta-analyses/reviews (Al-Inany [2003, 2005, 2008, 2009], Westergaard, Coomarasamy, Afnan), four were excluded as duplicate publications (Plateau [2004, 2008], Smitz, Ziebe) and three studies were excluded because of insufficient details (Elwin [unpublished data], Loutradis, Strowitski) [1,2,13,18,23,26,30-32,42-45]. The 16 remaining studies which were truly or quasi-randomized met the inclusion criteria and were found to be of acceptable internal validity [5,14-17,19-22,24,25,27-29,46,47].…”
Section: Resultsmentioning
confidence: 99%
“…Combined with sensitivity analyses, our method of trial selection provided a robust number of studies (n = 16) compared to prior meta-analyses which included between 4 and 12 studies comparing hMG and r-hFSH [13,18,23,26,30,31]. As a result of the large sample size of this meta-analysis, and the fact that several endpoints were considered, the level of significance was set at P < 0.01.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The search results were cross-checked against publications listed in previous meta-analyses [15-19] to ensure that all relevant studies were included.…”
Section: Methodsmentioning
confidence: 99%
“…Multiple studies have been done to prove the superiority of a distinct gonadotropin preparation, with very conflicting results. 85,[87][88][89][90][91][92] These differences can be traced back, at least partly, to the incomplete downregulation through the GnRH agonists or antagonists, where secretion of LH continues to be detectable 93,94 in varing amounts. 95 No doubt has been raised about the necessity of a distinct amount of LH to ensure the resumption of meiosis, 96 the most crucial process to achieve full chromosomal integrity and oocyte diploidy.…”
Section: Gonadotropin Stimulation In Ivf Patients As a Lh Depleted Modelmentioning
confidence: 99%